Severe Adverse Toxic Effects of Low-Dose Methotrexate Treatment on an Ectopic Pregnancy Patient With Methylenetetrahydrofolate Reductase Mutations: A Case Report - Yu, Huan; Wang, Wenhui; Liang, Haiyan; Wang, Kun; Ling, Bin (Frontiers in Medicine, 2021)
Background: Low-dose-MTX(LD-MTX) has been widely used for the treatment of the ectopic pregnancy (EP) for many decades and related severe adverse toxic effects are rare. Current studies have shown that polymorphisms of methylenetetrahydrofolate reductase (MTHFR) gene can decrease the MTX clearance, leading to the metabolite accumulation. However, the gene mutations are still blank in EP about severe adverse toxic effects. Case presentation: We report a rare case of a 38‐year‐old female who developed persistent fever, grade IV myelosuppression, skin lesions, mucositis, and liver injury after single dose of LDMTX to treat EP. The personalized genetic testing showed that MTHFR TT (677C>T) and MTHFR AA (1298A>C) were detected. The symptoms gradually improved after calcium leucovorin (CF) rescue, continuous renal replacement therapy (CRRT), promoting blood system regeneration, and multiple supportive treatments. Conclusion: This is the first report on serious adverse toxic effects of LD-MTX on an EP patient with MTHFR mutations. This case showed that the unexpected life-threatening toxicity with LD-MTX should be highly considered and early recognition. In particular, some easily overlooked gastrointestinal, skin, and mucosal symptoms occur earlier than severe myelosuppression. When toxic effects suspected, detecting the polymorphisms of MTHFR gene and monitoring MTX concentration in blood could assist us to formulate individualized and active treatments. Although rare, but life-threatening adverse toxic effects of LD-MTX can also remind clinicians to be more cautious, and fully explanation of the related risk factors for patients with EP before MTX treatment is highly essential.